Carbon dioxide diffuse degassing as a tool for computing the thermal energy release at Cerro Blanco Geothermal System, Southern Puna (NW Argentina). (January 2021) - Lamberti, M.C.; Chiodi, A.; Agusto, M.; Filipovich, R.; Massenzio, A.; Báez, W.; Tassi, F.; Vaselli, O.
Abstract: This work presents the first carbon dioxide diffuse degassing survey carried out in the Cerro Blanco Geothermal System (CBGS; Southern Puna plateau, NW Argentina) with the aim to estimate the thermal energy release. The survey was divided into (i) a prospecting stage of the degassing sites within the CBGS and (ii) mapping of the selected diffuse degassing sites. The purpose of the prospecting stage was to elaborate two transects, crosscutting the nested caldera of Cerro Blanco Volcanic Complex (CBVC) and Los Hornitos thermal site, both belonging to CBGS. More than 60 soil diffuse CO2 flux and soil temperature measurements were carried out in the 16-km and 1-km long transects. Significant soil diffuse emissions were only found within the Cerro Blanco caldera, where a detailed mapping of CO2 flux was produced. In this site, named CBa, a single diffuse degassing structure releasing 22.44 kg d −1 of deep-sourced CO2 into the atmosphere was identified. Any other geologic feature of the CBVC and Los Hornitos hydrothermal site presented very low CO2 flux values. According to statistical and geochemical analyses, soil diffuse CO2 degassing is fed by a deep-seated (hydrothermal) and a soil respiration source, which mix each other at different degree. The thermal energy release associated with the diffuse degassing process at CBa is estimated to be ~2.4 kJ/s. This low magnitude thermal energy release is probably a consequence of an efficient cap-rock that likely buffer the surficial expressions of the geothermal resource potentially occurring at depth. Highlights: Cerro Blanco Geothermal System emits diffuse carbon dioxide through a single diffuse degassing structure. The diffuse emission and the thermal is significantly low if compared with other volcanic and geothermal Andean areas. Background CO2 fluxes can be partitioned into biotic and abiotic components.